The effects of whole body hyperthermia on the pharmacokinetics and toxicity of the basic 2-nitroimidazole radiosensitizer Ro 03-8799 in mice. - Walton, M. I. (1987)
We have investigated the effects of 50 min whole-body hyperthermia (WBH; 15 min equilibration followed by 41 degrees C for 35 min) on the toxicity and pharmacokinetics of the radiosensitizer Ro 03-8799 in mice. WBH markedly reduced Ro 03-8799 LD50/7d from 779 to 259 micrograms g-1 (P less than 0.001). Pharmacokinetics were studied at 175 micrograms g-1 (approximately 0.6 WBH LD50/7d) with and without heat and 437 micrograms g-1 (approximately 0.6 control LD50/7d) without heat. WBH increased Ro 03-8799 plasma concentrations and prolonged its elimination t1/2 by 26% (P less than 0.01). Total plasma area under the curve (AUC0-infinity) was increased by 22%, but was still less than 50% of the unheated high-dose value. Ro 03-8799 concentrated 300-400% in tumour and brain relative to plasma. Absolute tumour and brain levels were unaltered by WBH, giving reduced tissue/plasma ratios. WBH greatly inhibited glomerular filtration (51Cr EDTA clearance) during heating, contributing to the increased plasma Ro 03-8799 concentrations. WBH increased peak plasma concentrations of the Ro 03-8799 N-oxide metabolite Ro 31-0313 by 61% and the beta-phase AUC of i.v. administered Ro 31-0313 by 36%. Since Ro 31-0313 levels were increased to a greater extent after Ro 03-8799 and WBH than Ro 31-0313 and WBH, WBH must both increase metabolite production and decrease its plasma clearance. WBH had no effect on Ro 31-0313 tumour concentrations or its exclusion from brain. These complex effects of WBH on Ro 03-8799 pharmacokinetics may contribute to the enhanced toxicity, possibly through hyperthermia-stimulated bioreductive drug activation, but do not wholly explain it.